Determinants of Female Bamboo Weaving Craftsmen's Labor Force Participation in Taman Sari Village, Gunung Sari District, West Lombok Regency - Abu Rizal Kholid; Gusti Ayu Arini; Ahmad Zaenal Wafik (Indonesian Development Economics and Localities, 2025)
This study aims to analyze wages, work experience, age, marital status and the presence of toddlers as determinants that influence the labor force participation of female bamboo weaving craftsmen in Taman Sari village, Gunung Sari sub-district, West Lombok regency. This type of research is quantitative explanatory. The data in this study are primary data with data collection methods using the census method. The population in this study were 34 female bamboo weaving craftsmen in Taman Sari village. The analysis model used in this study was multiple linear regression. The results of the study showed that the wage variable partially had a significant and positive effect on women's work time, the work experience and marital status variables partially did not have a significant and positive effect on women's work time, the age and presence of toddlers variables partially did not have a significant and negative effect on women's work time. The results of the study simultaneously showed that the variables of wages, work experience, age, marital status and the presence of toddlers together had a positive and significant effect on women's work time. It is hoped that the government can facilitate job training programs so that workers, especially female craftsmen, have specific skills and are motivated to develop their capacity.